PENGEMBANGAN MEDIA VIDEO ANIMASI TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SD - pirda amalia; Beta Rapita Silalahi (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2023)
This study aims to: (1) produce learning animation video media for fourth grade elementary school students, (2) determine the feasibility of animated video media on Theme 7, the beauty of diversity in my country for fourth grade elementary school students. From the results of the feasibility validation by material experts, media experts and learning experts. This research is a type of research and development with reference to development (R&D) with a 4D model which is an extension of Define, Design, Development and Dissemination. The instrument used to collect data is a questionnaire. The data analysis technique, namely descriptive qualitative, was converted into quantitative data. Based on the explanation that is divided into 3 aspects above, the average overall assessment of the teacher's response to the media is obtained by a percentage of 86.6%. This percentage includes very valid criteria (very feasible) to be used as a medium in learning activities for fourth grade elementary school students with the theme of the beauty of diversity in my country. Based on the explanation that is divided into 4 aspects above, the average overall assessment of media expert reviews gets a percentage of 82%. This percentage includes very valid criteria (very feasible) to be used as a medium in the learning activities of fourth grade elementary school students with the theme of the beauty of diversity in my country. Based on the explanation that is divided into 4 aspects above, the average overall assessment of the material expert's review gets a percentage of 80%. This percentage includes valid criteria to be used as a medium in the learning activities of fourth grade elementary school students with the theme of the beauty of diversity in my country.